Has carbon finance been able to promote clean energy development? — a low-carbon technology innovation perspective - Cui, Rui; Hao, Yuanyuan; Jiang, Yifei; Zhang, Haonan; Lv, Shuang (Frontiers in Environmental Science, 2025)
In recent years, with the increasing attention to global warming, low-carbon development has become a global requirement, which has attracted widespread attention from scholars and policymakers around the world. Therefore, this study explores the evolution of spatio-temporal dynamics and heterogeneity of the impact of carbon finance on clean energy development using spatial econometric modelling based on panel data from 30 provinces in China from 2010–2023, and also further explores the role of low-carbon technological innovations in this promotion process. It is found that carbon finance significantly promotes clean energy development, but this contribution decreases with the intervention of low-carbon technology innovation. Secondly, when considering government intervention and market-driven conditions, both amplify the positive impact of carbon finance on the development of clean energy, and the impact of carbon finance varies in different regions. Finally, considering the existence of spatial and regional heterogeneity, carbon finance has the largest impact among the eastern regions, the lowest among the central regions, and the second largest among the western regions. These facts indicate how carbon finance can be an effective means to support the development of clean energy in China. Therefore, in promoting the deep convergence of both carbon finance and clean energy, this study provides theoretical support for rising emerging developing economies such as China.